University research for sustainable development: definition and characteristics explored - Waas, T.; Verbruggen, A.; Wright, T. (Journal of cleaner production, 2010)
University research is pivotal for sustainable development, but to succeed, new ways of conducting research are needed. Only recently has the field of “sustainability and higher education” (SHE) started to deal with the issue. In this paper we define “university research for sustainable development” comprehensively as “ all research conducted within the institutional context of a university that contributes to sustainable development”, and propose a set of twenty two preliminary characteristics of this concept. We provide foundational information in particular for various university stakeholders, and those of higher education in general, considering the (re)orientation of research towards sustainable development and offer a beginning of dialogue on the subject, within SHE.